Conhecimentos indígenas e educação em ciências: a sexualidade Kambeba como elemento de preservação cultural - Mota, Dalva Suely Moraes (2013)
The valuation of intangible assets of traditional peoples is a fundamental factor for the preservation of culture, which prompted us to research on the topic of sexuality among indigenous Indians Kambeba, in the lower Rio Negro, Amazonas. Based on the habits and knowledge of the culture of this people, we proposed a reflection, based on intercultural dialogues, Amazon’s own reality. We found that the indigenous culture remains active in certain ethnic groups, although inhibited the development of their creativity and potential traditional, especially with regard to sexuality. We describe habits, beliefs and myths concerning sexuality indigenous Kambeba, highlighting their sociocultural and historical tours, doing an analysis on the influence of the surrounding society in transformation or preservation of this ethnography. Highlight the relevance of the theme for the Teaching of Science, considering how much we can learn with the customs and habits of the native culture Kambeba and his way of dealing with sexual issues, charting new paths between the (mis) direction of a people poor and explored since colonial times. It is therefore a qualitative, exploratory type, with ethnomethodological traits as it focuses on a specific feature of a particular ethnicity and traditions. The interdisciplinary approach of the curriculum in Indigenous School Aua Three States permitted to observe the development of intercultural projects, in which the school operates as a living space for strengthening and recovery of traditional knowledge of the people and as a means Kambeba articulator promotion of theoretical knowledge national society.